THE RUBAS FORTIFICATION OF THE MID 6TH CENTURY: FEATURES OF THE STRUCTURE OF THE EASTERN FACADE OF WALL 2 - Gmyra, Ludmila Borisovna (History, Archeology and Ethnography of the Caucasus, 2021)
The Rubas fortification is a unique complex of stone military-engineering structures, built in the lower reaches of the River Rubas, 20 km west of the Caspian Sea coast and the same distance southwest of the Derbent Pass. In terms of the main indicators (monumentality and functional orientation), it belongs to a series of defensive lines of the Western Caspian region, erected by Persia with the assistance of Byzantium during the era of the Great People’s Migration. Typologically and chronologically, it has analogies with the fortress structures of Derbent, dating back to the 6th century. Its uniqueness is justified by the presence of monumental military-engineering structures of various parameters in terms of design and layout, united by construction links into a single object. Each structure carried a separate function, complementing the general tasks of a defensive nature. The structure of the eastern facade of Wall 2 is of combined nature, since it comprises of several different types of sections. The present article considers the features of building techniques for the construction of the facade of a monumental wall of a defensive structure, which are distinguished by a main direction. The purpose of this study is to analyze engineering solutions and to determine the functional tasks of each object included in the eastern facade of Wall 2. Research methods include detail analysis of techniques of erecting the eastern facade of Wall 2, substantiation of presence of various structure parts of its sections and identification of functional purpose of the synthesis system of the facade’s structure of the main wall. Analysis of materials of the structurally complex defensive object of the Rubas fortification of the middle of the 6th century, which is the main monumental Wall 2, namely its outer eastern facade, shows that the complex of engineering solutions of this structure was mainly due to the volume of external loads and the strategy of assault on a particular enemy, which at that time were the nomadic Turkic-speaking tribes who used Derbent passage for military operations in the Caucasus and the Middle East.